Bioethanol Technologies 2021
DOI: 10.5772/intechopen.94358
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Ethanol Production from Fruit and Vegetable Waste by Using Saccharomyces cerevisiae

Abstract: Waste from the food is a challenge to the environment all over the globe, hence there is need to be recycled. Vegetables and fruits biomass is a resource of renewable energy with significant fuel source potential for the production of electricity and steam, fuel for consumption and laboratory solvents. Bioethanol derived from biomass contributed 10–14% of the total world energy supply and solved the world crisis such as global warming and depletion of fossil fuel. Presently, bioethanol is a global issue on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…Finally, the percentage of lignin content in the sample was estimated using equation ( 4). Te percentages of other components that existed in the sample were estimated using equation (5). Te quantitative methods used in the analysis of the chemical compositions of the CH and BSG fbers are mentioned in Table 1.…”
Section: Determination Of Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the percentage of lignin content in the sample was estimated using equation ( 4). Te percentages of other components that existed in the sample were estimated using equation (5). Te quantitative methods used in the analysis of the chemical compositions of the CH and BSG fbers are mentioned in Table 1.…”
Section: Determination Of Ligninmentioning
confidence: 99%
“…Te cofee husk of cofee Arabica has been widely studied for diferent applications [4]. For example, it was used as a feedstock for bioethanol production [5], as a food supplement in "energy drinks" [6], and also as a reinforcement agent in recycled polypropylene [7] and polyhydroxybutyrate composites [8]. CH fbers of cofee Arabica consist of cellulose (30-35%), hemicellulose (18-21%), lignin (19-22%), and other components (25-28%), such as waxy, organic, and inorganic components [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term criticisms of bioethanol production from first‐generation feedstocks (particularly food crops) stimulated shifting to non‐edible biomass, and this makes biofuel an attractive option to replace fossil fuels due to its renewability, cost‐effectiveness, and contribution to alleviating the energy crisis and environmental pollution 215 . The study by Khandaker et al 216 . and many other research findings reported that any fruit wastes and byproducts that are rich in fermentable sugar and carbohydrates are potential feedstocks or substrates for bioethanol production.…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 99%
“…For instance, in the study conducted by Khandaker et al 216 . in Malaysia, the bioethanol production potential of fruits (pineapple and orange) and other two vegetables (potato and tomato) using Sacchromyces cerevisiae was reported and the pineapple waste/byproducts generated the highest (5.37%) yield followed by tomato wastes (5.07%).…”
Section: Fruit Waste and Byproduct Valorization Into Biofuelsmentioning
confidence: 99%
See 1 more Smart Citation